46.2k views
4 votes
Complete the table below for the equation y = x^2 + 2x - 1. Then, graph the equation on the provided graph grid.

Complete the table below for the equation y = x^2 + 2x - 1. Then, graph the equation-example-1
User Kapoue
by
5.6k points

1 Answer

6 votes

Answer:

y = x^2 + 2x - 1

x = -4

y = -4^2 + 2(-4) - 1

y = 16 + (-8) - 1

y = 7

x = -3

y = -3^2 + 2(-3) - 1

y= 9 + (-6) - 1

y = 2

x = -2

y = -2^2 + 2(-2) - 1

y = 4 + (-4) - 1

y = -1

x = -1

y = -1^2 + 2(-1) - 1

y = 1 + (-2) - 1

y = -2

x = 0

y = 0^2 + 2(0) - 1

y = 0 + 0 - 1

y = -1

x = 1

y = 1^2 + 2(1) -1

y = 1 + 2 -1

y = 2

x = 2

y = 2^2 + 2(2) - 1

y = 4 + 4 - 1

y = 7

User Kellen Stuart
by
5.9k points